Does Implementing Cryptography in Financial Risk Management Systems Reduce Data Security Risks – Literature Study - Gultom, Riris Rollyna (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
ABSTRACT This study investigates the use of cryptography in financial risk management systems to determine how well it mitigates data security risks. A key issue raised is the increasing threat to the integrity and privacy of financial data in the digital age, which requires more robust and flexible protection mechanisms. The objective is to determine the extent to which cryptographic techniques can enhance financial risk management systems and mitigate the possibility of data leakage and manipulation. The approach used is a literature review of various academic journals, scientific publications, and industry reports that discuss the integration of cryptography in the financial and information security domains. The study's findings indicate that cryptographic algorithms, such as AES, RSA, and blockchain-based encryption, can increase system resilience against cyberattacks while enhancing audit trails and access control. The implication of these findings is that the use of cryptography not only enhances data security but also increases stakeholder confidence in digital financial systems. To address the increasingly complex challenges of data security, this study suggests the creation of a set of cryptography policies and implementation standards integrated within a financial risk management framework. The analysis shows that cryptography plays a crucial role in maintaining the confidentiality, integrity, and authentication of financial data and can strengthen risk control systems against data leaks and manipulation. However, there is a gap in the literature regarding the integration of cryptography with a comprehensive risk management framework, as well as a lack of comparative evaluation of the effectiveness of various cryptographic techniques in the context of financial operations. Keywords: Blockchain; data security; cryptography; digital financial system; encryption